الحواشي الأصوليَةّ الحنفيَةّ في عهد الخلافة العثمانَيةّ - Hüseynî, Velid İbrahim (Fatih Sultan Mehmet Vakıf Üniversitesi, 2020)
شهدت الحقبة العثمانيَة في بعض مراحلها نهضة علميَّة عظيمة، وقد شهدت سنوات الازدهار منها ظهورَ مدارسَ جليلةِ القدر في بقاع كثيرةٍ من أراضي الدولة العليَة، وكثر فيها التأليف في علوم الشريعة كلِّها، وفتِحت مكتباتٌ عامّةٌ لحفظ المؤلَفات ونسخِها، وكان المذهب الأكثر انتشارًا هو المذهب الحنفيُّ، كونه المذهب الرسميَ للدولة، ولذلك كثُرت فيه التآليفُ.ّ ويلاحظ في هذا العصر كثرة )الحواشي( في شتى العلوم وانتشارها، وهي طريقة تأليف تُعتبر جديدةً نسبيًّا، حيث لم تظهر إلا مطلعَ القرن السابع الهجريِّ، وقد فُقدت في عصرنا أو كادت، وفتَرَتْ همّةُ طلبة العلم عن قراءتها رغم أهميتها. فمن أجل ذلك كتبت هذا البحث لأُبيِّنُ فيه جهودَ علماء الحنفيَة في كتابة الحواشي في علم أصول الفقه، وأهمية الحواشي للعلماء وطلبتهم، وبيَنت دعم السلاطين للعلم والتأليف والمدارس، ورددت على من انتقد الحواشي، وذكرت أسماء الحواشي والكتب التي ألِّفت الحواشي عليها، مع بيان التواريخ وأسباب التأليف واهتمام العلماء بكتب معينة أكثر من غيرها.

Elhamdulillah, vessalâtu vesselâmu alâ seyyidinâ Muhammedin ve alâ âlihî ve sahbihî ecmaîn. Şüphesiz ki Osmanlı Devri bazı dönemlerinde önemli ilmî kalkınmalara ve yükselme yıllarına şahitlik etmiştir. Bunlardan bazıları: Osmanlıda önemli sayılan birçok bölgede büyük değer taşıyan medreselerin açılması aynı zamanda şeriat ilimlerinin tamamını kapsayan kitap yazımlarının artması ve yazılan bu kitapların ve nüshalarının korunması için genel kütüphanelerin açılmasıdır. Tüm bunlar içerisinde en yaygın olan mezhep ise devletin resmî mezhebi olması hasebiyle Hanefî mezhebi idi. Bunun için de Hanefîlik üzerine yazılan kitaplar artmıştır. Bu dönemde dikkat çeken şey ise farklı ilimlerde yazılan dipnotların çokluğu ve yaygın olmasıdır. Aynı zamanda dipnot yazımı o dönemde yeni bir metod sayılmaktaydı öyle ki hicri yedinci asrın başına kadar ortaya çıkmamıştı. Günümüzde ise ilim talebesi yazılan dipnotların önemine rağmen okumayı ihmal etmekte ve bu dipnotlar kaybolmak üzeredir. İşte bu araştırmayı, Hanefî âlimlerinin Fıkıh Usûlü ilminde dipnot yazarken göstermiş olduğu emekleri ve bu dipnotların ulemâ ve talebesi için önemini açıklamak için yazmış bulunmaktayım. Aynı zamanda araştırmamda; sultanların ilme, kitap yazımına ve medreselere vermiş oldukları desteği de belirtmiş olmakla beraber yazılan dipnotları eleştirenlere de reddiyede bulundum. Ve yazılan dipnotların yahut üzerine dipnot yazılan kitapların isimlerini zikredip tarihlerini, yazılma sebeplerini ve âlimlerin başka kitaplardan ziyade özellikle belirli kitaplara vermiş oldukları önemi açıkladım.

Praise be to God and prayers and peace be upon our master messenger Prophit Muhammad and on his family and companions. Hereafter, The Ottoman period has witnessed at some stages a great scientific renaissance. The years of prosperity witnessed the emergence of great schools in many parts of the lands of the high state, where there was a great deal of authorship in all the sciences of Shari’a, and public libraries were opened for the preservation and reproduction of the scientific works. Hanafi, was widely spread during that eara being the official doctrine of the state, and therefore there were a clear increase in auothering and publications. It is noted that during that era a noticilbe increase and wide spread of (the footnotes) in the various sciences. Footnotes as a method of authorship is considered new at that time, which did not appear until the beginning of the seventh century AH. The footnotes has been lost or almost lost in our time, and the eagerness of students to read them, has remarkabley deceased despite their importance. For this reason I have researched this topic and authored this paper to show the efforts of the Hanafi scholars in writing the footnotes in the jurisprudence of the field of Usool Alfiqih and the importance of the footnotes to the scholars and their students. I have also showed the support of the sultans for science, authoring and writing and to the schools and education in general. I also replied to the critizisom and on those who criticized the footnotes. I have also mentioned the names of the footnotes and the books on which were written on footnotes, showed the dates of those publictions, reasons behind their authorship and why some of those publications attracted more attention of scholars more than others.
Osmanlı Devrinde Hanefî Fıkıh Usûlü İlminde Yazılan Dipnotlar
Footnotes Of Fundamentalist Hanafi In The Ottoman Era
Keywords: الحاشية; الحواشي; أصول الفقه; المذهب الحنفي; الدولة العثمانية; Haşiye; Haşiyeler; Fıkıh Usulü; Hanefi Mezhebi; Osmanlı Hilafet; Footnotes; Fundamentals of Fiqh; Hanafi School of Thought; Ottoman Empire